Toward an integrated approach for addressing malnutrition in Zambia: a literature review and institutional analysis - Harris, Jody; Drimie, Scott (International Food Policy Research Institute, 2012)
Due to the predominance of direct, specific interventions in nutrition for development, the health sector tends to own nutrition, with interventions customarily implemented through health programs. The premise that the agriculture sector should also be a vehicle for improved nutrition is intuitive, but this sector often delivers neither good nutrition nor food security to the most vulnerable in the population. The complex and multisectoral nature of malnutrition may explain why it has not been effectively addressed. Though we know many of the solutions, such as intersectoral action which is critical to addressing this complexity, to date there is no consensus on how intersectoral solutions are best implemented or institutionalized. This review brings together experiences from across Sub-Saharan Africa in order to draw out recommendations for improved intersectoral implementation going forward, and assesses how these findings apply specifically to the Zambian context.